Surgical Strategy in Multicentric Breast Cancer: A Comparative Analysis of Mastectomy vs Mastectomy on Demand Following Neoadjuvant Chemotherapy - Surya Martua Horas Harahap (GLOBAL HEALTH SCIENCE GROUP, 2026)
The management of multicentric breast cancer (MBC) has traditionally relied on total mastectomy to ensure comprehensive local control. However, the use of neoadjuvant chemotherapy (NAC) has transformed this approach by frequently achieving significant tumor downstaging or even a pathological complete response (pCR). This has spurred a critical re-evaluation of surgical strategies, moving from a standard, one-size-fits-all mastectomy to a more personalized approach. To evaluate the effectiveness of neoadjuvant chemotherapy (NAC) in downstaging multicentric breast cancer and to assess the feasibility of breast-conserving surgery compared to total mastectomy, based on pathological response and tumor characteristics. This literature review provides a comparative analysis of standard mastectomy versus a mastectomy on demand strategy for MBC patients following NAC. The review synthesizes findings from existing observational and retrospective studies to highlight key differences in oncological outcomes, cosmetic results, and patient quality of life. It also critically evaluates the current literature to identify major research gaps and areas for future investigation. The literature review draws upon a diverse selection of peer-reviewed international journals, including Clinical Breast Cancer, BMC Cancer, NPJ Breast Cancer, Annals of Surgical Oncology, and British Journal of Surgery. A total of 26 references were cited, with approximately 20 forming the core foundation for comparative analysis between standard mastectomy and mastectomy-on-demand strategies following neoadjuvant chemotherapy in multicentric breast cancer (MBC). References span from 2022 to 2025, reflecting reliance on recent and clinically pertinent sources. Studies were critically appraised using a narrative synthesis approach, emphasizing thematic relevance to oncological outcomes, cosmetic considerations, patient quality of life, and clinical decision-making. The review identifies key differences in surgical strategies, evaluates the role of post-NAC imaging and pathological assessment, and underscores gaps in standardized patient selection protocols and prospective clinical trials. A standard mastectomy, while a cornerstone for local control, is increasingly recognized as a maximalist approach that may be unnecessarily extensive for some patients, leading to significant psychosocial and physical morbidity. In contrast, the mastectomy-on-demand strategy leverages a favorable response to NAC to allow for less radical, aesthetically-sparing procedures. The primary challenge for this approach is the need for highly accurate post-NAC imaging and pathological assessment to ensure oncological safety and clear surgical margins. The literature reveals a notable lack of large-scale prospective trials and standardized protocols to guide patient selection for this personalized strategy. The evolving management of MBC reflects a fundamental shift towards a patient-centered approach that balances local disease control with quality of life.